MOTIVES AND MOTIVATION OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS TO RESEARCH ACTIVITY AND WAYS OF ITS INCREASE - Notchenko, Viktoriia; Dyatlov, Yuriy (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This article examines and summarizes the views of the authors involved in the study of student participation in research activities. The concept of "motivation for research activity" is specified, the content of scientific research as a special type of intellectual activity of a person is characterized. Further, the authors on the basis of the method of interviewing collected, analyzed and summarized the material, which allowed to identify the motives that encourage students of higher educational institutions to participate in activities of a scientific and research nature. The main motives were defined: the remunerations received by the student as a result of participation in scientific research; the desire to realize the existing abilities for scientific activity; disclosure of other abilities or satisfaction of other needs for which research activity is a means to achieve goals. Also, the authors identified the lack of interest on the part of students to research activities, formulated and justified the reasons for the lack of motivation of students to this activity. According to the results of the study, recommendations were developed, the introduction of which in the educational process will increase the motivation of students to research activities carried out independently or under the guidance of experienced teachers and researchers of higher educational institutions.